Evinacumab for the treatment of homozygous familial hypercholesterolaemia: first patient case report in Switzerland (Swiss Medical Weekly, 2025)
We present the first case in Switzerland of a patient with homozygous familial hypercholesterolaemia treated with evinacumab, a new recombinant human monoclonal antibody currently approved in Europe and in the USA but not yet in Switzerland. Homozygous familial hypercholesterolaemia is a rare genetic disorder that causes severely elevated levels of low-density lipoprotein (LDL) cholesterol and early atherosclerotic cardiovascular disease, which, if left untreated, can lead to premature death. As a result of this newly introduced treatment, the patient’s LDL cholesterol levels were reduced by more than half, achieving recommended target values of secondary prevention for the first time. This case underscores the efficacy of evinacumab in achieving LDL cholesterol targets in homozygous familial hypercholesterolaemia patients and highlights the importance of early identification and treatment initiation.